Improvement of early developmental competence of postovulatory‐aged oocytes using metaphase II spindle injection in mice - Tatsuyuki Ogawa; Hiroko Fukasawa; Shuji Hirata (Reproductive Medicine and Biology, 2020)
Abstract Purpose Assisted reproductive technology (ART) is a widely applied fertility treatment. However, the developmental competence of aged oocytes from women of a late reproductive age is seriously reduced and the aged oocytes often fail in fertilization even when ART is used. To resolve this problem, we examined usefulness of a new method “the metaphase II spindle transfer (MESI)” as ART using mouse oocytes. Methods This work was composed of two experiments. First, 24 hours after collection, embryos from oocytes (1‐day‐old oocytes, called postovulatory‐aged oocytes), were observed, after intracytoplasmic sperm injection (ICSI), and it was found that they were not able to reach the blastocyst stage. Next, the metaphase II chromosome‐spindle complexes from 1‐day‐old oocytes were injected into cytoplasts from oocytes just collected, using piezo pulses to generate reconstructed oocytes. This procedure was named metaphase II spindle injection (MESI). Results After ICSI, embryos from the reconstructed oocytes (32/105), which contained the genes of 1‐day‐old oocytes, were able to develop into the blastocyst stage. The fragmentation rate after ICSI was 28.6%. Thus, the developmental competence of 1‐day‐old oocytes was improved by MESI. Conclusions The MESI method has the potential to improve the success rate of infertility treatments for women of a late reproductive age.